Letter from Joseph P. Comegys to James Curtis Booth, May 20, 1885 - Comegys, Joseph P. (Joseph Parsons) (1885)
Joseph P. Comegys (1813-1893), an American judge, lawyer, and politician from Dover, Delaware, sends James Curtis Booth (1810-1888) an Act of Assembly related to his work with the Delaware Geological survey as offered in his letter of May 9.
Keywords: Booth, James Curtis, 1810-1888; Comegys, Joseph P. (Joseph Parsons), 1813-1893; Delaware Geological Survey; Geological surveys; United States Mint; Mint of the United States